2022
DOI: 10.1177/14574969211070668
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for major amputation after arterial vascular trauma of the lower extremity

Abstract: Background & objective: Arterial vascular trauma bears a great risk of poor functional outcome or limb loss. The aim of this study was to analyze amputation rates of patients after vascular trauma and to perform a predictor analysis for the risk of major amputation. Methods: In a single-center retrospective analysis of 119 extremities treated for arterial vascular injury between 1990 and 2018 amputation rates and factors associated with limb loss were assessed. All patients were treated for traumatic vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(29 reference statements)
1
2
0
1
Order By: Relevance
“…Many prior studies have documented risk factors for amputation including soft tissue injury, open fracture, nerve injury as well as blunt mechanism of trauma. [1][2][3][5][6][7][8][9][10] Our study shows similar patterns including open fracture and blunt mechanism. Signs of ischemia on presentation (absent Doppler signals) were also associated with amputation in our study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Many prior studies have documented risk factors for amputation including soft tissue injury, open fracture, nerve injury as well as blunt mechanism of trauma. [1][2][3][5][6][7][8][9][10] Our study shows similar patterns including open fracture and blunt mechanism. Signs of ischemia on presentation (absent Doppler signals) were also associated with amputation in our study.…”
Section: Discussionsupporting
confidence: 74%
“…13 All patients who underwent amputation due to arterial bypass graft thrombosis presented with signs of ischemia and multiple tibial vessel injuries which have been noted to be risk factors for amputation in prior studies. [1][2][3]7 Urrecehga et al reported a 12% revascularization failure rate resulting in amputation in patients with traumatic lower extremity arterial injury. 14 Five of our patients presented with signs of ischemia (absent Doppler signals and pulse).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Điều này cũng tương đồng với nghiên cứu của tác giả Hoàng Anh Công (2020) ghi nhận kết quả điều trị trên 33 bệnh nhân chấn thương động mạch khoeo có 93,95% bệnh nhân không ghi nhận biến chứng sau mổ [9]. Nghiên cứu của tác giả Kluckner M năm 2022 trên 118 bệnh nhân ghi nhận tỉ lệ cắt cụt chi là 16,8% [10].…”
Section: Kết Quả đIều Trị Chấn Thương độNg Mạch Khoeounclassified